Air cushion film, barrier paper air cushion and preparation methods of air cushion film and barrier paper air cushion
By adopting a multi-layer structure air cushion film, combined with the design of talc-modified plastic particles and PBAT materials, the problem of difficult to take into account in the existing technology of biodegradability and barrier gas protection performance, and an efficient, environmentally friendly and economical air cushion is achieved. Film production.
Patent Information
- Application Number
- CN202411484522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Existing barrier paper air cushion products are difficult to balance between biodegradability and barrier gas protection performance, resulting in poor environmental pollution and protection effects.
The air cushion film with a multi-layer structure is composed of modified plastic particles wrapped in talc powder on the surface. The middle and inner layers contain PBAT materials and are prepared by multi-layer coextrusion blown film technology, combined with hot pressing production process to improve production Efficiency and cost reduction.
The biodegradable properties of the air cushion film and the barrier and gas protection effect that is no less than nylon are achieved, while reducing production costs and carbon emissions, achieving a win-win situation between environmental protection and economy.
Smart Images

Figure CN119459081A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air cushion films, and in particular to an air cushion film, a barrier paper air cushion and preparation methods thereof. Background Art
[0002] At present, barrier paper air cushion products are mainly made of PE (polyethylene) / PA (polyamide) materials, which are composited with kraft paper by glue. This structure gives the product good barrier, air retention and puncture resistance, ensuring the stability and protection of the air cushion during packaging and transportation. However, the compatibility and processing temperature differences between PE and PA materials make these materials difficult to recycle after being discarded, and they are not biodegradable, which brings serious pollution problems to the environment.
[0003] Most of the biodegradable materials on the market are modified from PBAT (polyethylene terephthalate-co-caprolactone). Although they have achieved the characteristics of biodegradability, their barrier properties are far inferior to PE / PA materials and cannot meet the needs of barrier and gas retention. Summary of the invention
[0004] In order to solve the problem that it is difficult to simultaneously take into account the biodegradability and barrier and air retention performance of barrier paper air cushion products in the prior art, the present invention provides an air cushion film, a barrier paper air cushion and methods for preparing the same.
[0005] In order to solve the above technical problems, one of the technical solutions provided by the present invention is as follows:
[0006] An air cushion film, comprising an outer layer, a middle layer and an inner layer;
[0007] The components of the outer layer include modified plastic particles with talcum powder coated on the surface, and the components of the modified plastic particles include PPC, PBAT and a molecular entanglement agent;
[0008] The components of the middle layer and the inner layer both contain PBAT.
[0009] In one embodiment, the components of the modified plastic particles coated with talcum powder on the surface include:
[0010] 50.0 wt. % to 80.0 wt. % PPC;
[0011] 15.0 wt % to 50.0 wt % PBAT;
[0012] 2.0 wt % to 5.0 wt % of a molecular entanglement agent;
[0013] 1.0 to 2.0 wt% talc.
[0014] In one embodiment, the particle size of the talc is above 2500 mesh.
[0015] In one embodiment, the components of the middle layer include PBAT, PLA, activated calcium carbonate, a molecular entanglement agent and calcium stearate.
[0016] In one embodiment, the components of the middle layer include:
[0017] 50.0 wt % to 65.0 wt % PBAT;
[0018] 8.0 to 15.0 wt % PLA;
[0019] 25.0 to 35.0 wt. % activated calcium carbonate;
[0020] 2.0 wt % to 5.0 wt % of a molecular entanglement agent;
[0021] 0.3 wt% to 0.5 wt% calcium stearate.
[0022] In one embodiment, the components of the inner layer include PBAT, PBST, and a lubricant.
[0023] In one embodiment, the components of the inner layer include:
[0024] 49.95 wt % to 65.0 wt % PBAT;
[0025] 34.8 wt % to 50.0 wt % PBST;
[0026] 0.05 wt % to 0.2 wt % of a lubricant.
[0027] The melt index of the PBAT used in the inner layer is below 5g / 10min, wherein the test method of the melt index is GB / T3682, and the test conditions are 190°C and 2.16kg;
[0028] The melt index of the PBST used in the inner layer is below 5g / 10min, wherein the test method of the melt index is GB / T3682, and the test conditions are 190°C and 2.16kg;
[0029] The second technical solution provided by the present invention is as follows:
[0030] A method for preparing an air cushion film comprises the following steps:
[0031] Providing an outer layer component, a middle layer component and an inner layer component, wherein the outer layer component comprises modified plastic particles with talcum powder coated on the surface, and the modified plastic particles comprise PPC, PBAT and a molecular entanglement agent;
[0032] The outer layer component, the middle layer component and the inner layer component are subjected to multi-layer co-extrusion blown film to form a film.
[0033] The third technical solution provided by the present invention is as follows:
[0034] A barrier paper air cushion, the barrier paper air cushion comprising an upper protective layer, an air cushion layer and a lower protective layer;
[0035] The air cushion layer adopts the air cushion film as described above;
[0036] The upper protective layer and the lower protective layer are kraft paper.
[0037] The fourth technical solution provided by the present invention is as follows:
[0038] The method for preparing the barrier paper air cushion as described above comprises the following steps:
[0039] The upper protective layer, the air cushion layer and the lower protective layer are stacked in order from top to bottom and pressed by a heated roller.
[0040] Based on the above, compared with the prior art, the air cushion film provided by the present invention not only has biodegradability but also has a barrier and air retention effect that is no less than that of nylon.
[0041] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.
[0043] Figure 1 A schematic diagram of bag making using upper and lower kraft papers and tubular film provided by the present invention;
[0044] Figure 2 A schematic diagram of rolling the paper air cushion before winding provided by the present invention;
[0045] Figure 3 A photo of a finished barrier paper air cushion provided by an embodiment of the present invention;
[0046] Figure 4This is a photo of a finished product of a barrier paper air cushion provided by another embodiment of the present invention. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in the different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] In the description of the present invention, it should be noted that all terms used in the present invention (including technical terms and scientific terms) have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and cannot be understood as limiting the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in the present invention.
[0049] The air cushion film provided by the present invention not only has excellent biodegradability, but also is not inferior to nylon materials in terms of gas barrier and air retention effect. In addition, the air cushion film can be applied to a new hot pressing production process when compounded with paper, which not only significantly improves production efficiency, but also greatly reduces the process flow of material and paper coating or laminating, thereby effectively reducing production costs and carbon emissions, achieving a win-win situation for environmental protection and economy.
[0050] An embodiment of the present invention provides an air cushion film, the air cushion film comprising an outer layer, a middle layer and an inner layer;
[0051] The components of the outer layer include modified plastic particles with talcum powder coated on the surface, and the components of the modified plastic particles include PPC, PBAT and a molecular entanglement agent;
[0052] The components of the middle layer and the inner layer both contain PBAT.
[0053] Specifically, the present invention uses the above components and structures as the outer layer of the air cushion film to have at least the following three effects:
[0054] First, the oxygen permeability of PBAT material is about 1500cm 3 / m 2 ·24h·0.1MPa, which does not have good barrier properties. Therefore, the present invention introduces PPC material, and the oxygen permeability of PPC material is about 20-30cm 3 / m 2 ·24h·0.1MPa, so that the outer layer material has obvious barrier and gas retention properties. In the prior art, in order to improve the compatibility of PPC and PBAT, thereby minimizing the impact of PBAT materials on the oxygen barrier properties of PPC, it is generally chosen to add a compatibilizer or a chain extender. Most of the compatibilizers on the market are made of PBAT as a base material and grafted with maleic anhydride materials. Their compatibility effect is general, and the amount added is large, which will further affect the barrier properties of PPC materials. Although the amount of chain extender added is small and can increase the molecular weight of the material, which meets the design requirements, the presence of the chain extender can easily cause local excessive polymerization and the appearance of crystal point particles, causing small pores to leak. Therefore, based on the above, the inventors have found that the use of molecular entanglement agents can solve the above problems well.
[0055] The main component of the molecular winding agent used in the present invention is a high molecular acrylate copolymer. Through the physical winding mode, the molecular chains between different materials are tied together like wool winding, which not only plays the purpose of compatibility, but also solves the problem of crystal point leakage caused by excessive local polymerization in the polymerization reaction. In order to ensure that the long chain of the high molecular acrylate copolymer has a good dispersion effect, a core-shell structure is formed on the surface of the high molecular acrylate copolymer so that it can be evenly dispersed in the material everywhere during the modification process. Specifically, it can be to disperse the oil phase mixture into tiny oil droplets through mechanical stirring or ultrasonic wave and other modes through materials such as PVDC, SAN, PAN, form a stable water-in-oil (W / O) or oil-in-water (O / W) emulsion, and then under certain conditions (such as heating, illumination, radiation, etc.), the initiator causes the monomer in the oil droplet to carry out polymerization reaction to form a high molecular chain. Along with the carrying out of the polymerization reaction, the high molecular chain is gradually deposited on the oil droplet surface to form a dense shell layer.
[0056] Secondly, the PPC material used in the present invention has a softening temperature of about 30°C and has a certain viscosity at room temperature. This characteristic will seriously affect the use in conventional film production, which is a major disadvantage of the material. Based on this disadvantage, the inventors found that when the material is used for the outer layer, it can be used to bond kraft paper, and thus creatively proposed a new paper air cushion production process.
[0057] Specifically, the steps of the production process are as follows:
[0058] Step 1, as shown in reference 1, kraft paper is placed on the upper and lower material racks, and the biodegradable tube film (made of the air cushion film provided by the present invention) is placed between the upper and lower kraft paper. The color and whether the kraft paper is bright are not limited, and the gram weight is 12-80g. If the thickness is too thin, the strength of the kraft paper will deviate, and it is easy to wrinkle when making bags. If the thickness is too thick, the heat conduction during bag making is poor, and the heat sealing effect of the film becomes poor.
[0059] Step 2: The thickness of the biodegradable tubular film should be 1C-7C. If the thickness is too thin, the film strength will deviate and it will be easy to wrinkle when making bags. If the thickness is too thick, the heat sealing effect between the film and the bottom kraft paper will be poor during bag making.
[0060] Step 3: After starting the machine, the three-layer material is pulled through the guide roller and received under the bag-making mold. The raised patterns on the surface of the bag-making mold are printed with gourd balls, squares, row structures, etc. The mold is heated to 120-260℃ to heat press the three-layer structure.
[0061] Step 4: The mold temperature is transmitted from top to bottom through the upper kraft paper to the biodegradable tubular film and the lower kraft paper in sequence. Under the action of temperature, the upper kraft paper and the biodegradable tubular film, and the biodegradable tubular film and the lower kraft paper are bonded, so that the three-layer structure becomes a whole.
[0062] Step 5: Use a toothed knife to print intermittent tooth marks on the surface of the three-layer structure that is heat-sealed together. This will make it easier to tear it apart for later use.
[0063] Step 6. Finally, roll it up into a roll. When using it, inflate and heat-seal it through the reserved inflation channel, and it can be expanded for use.
[0064] Under the heat pressure of the heat-sealing mold, the upper and lower kraft papers of the three-layer structure are bonded together with the biodegradable film along the heat seal, eliminating the laminating process and glue of the laminating paper, and having better strength than the laminating process. However, the disadvantage of this process is that the film and the kraft paper are separated at the position without the heat-sealing line. For this reason, the present invention utilizes the low softening point of PPC and adjusts the ratio of PPC to PBAT materials to control the softening point of the outer layer at 60-80°C. In this way, on the one hand, it will not cause the problem of film sticking during the film blowing process, and on the other hand, the reference Figure 2 As shown, upper and lower heating steel wheels are added before bag making and rolling, with a heating temperature of 120-140°C. The finished product is heated by rolling, so that the surface material of the film softens and becomes sticky, and adheres to the surface kraft paper.
[0065] There are two ways to produce traditional paper air cushion products. One is to coat a layer of degradable material on the kraft paper material, and then make bags with the coated material to produce paper air cushions. The other is to glue the kraft paper and the degradable film together with glue, and then use the coated paper to make bags to produce paper air cushions. Among them, the coating process temperature is generally above 260°C, which can easily lead to degradation of the degradable material, and the film lacks lateral stretching and has average orientation performance. Although the performance of the coated material can meet the needs, the required film has high flatness, the production process is difficult, the scrap rate is high, and the adhesive glue is non-degradable.
[0066] Third, although pure PPC material has better barrier properties, it is easy to delaminate from the middle layer material. Therefore, adding an appropriate proportion of PBAT to the outer layer can not only control the softening point of the outer layer, but the presence of PBAT can also make it easier for the outer layer and the middle layer materials to form a close bond and avoid delamination.
[0067] Moreover, in the preparation of the outer layer, the present invention specifically adds talcum powder after granulation so that it is wrapped on the surface of the modified plastic particles. This is because talcum powder has a smooth effect due to its unique flaky structure, and the modified PPC has a high temperature when it is stretched and granulated, and is prone to produce sticky blocks, so adding a small amount of talcum powder to wrap the surface of the particles after granulation can prevent the materials from sticking together. At the same time, it is found from the test process that the flaky structure of talcum powder does not affect the barrier properties of PPC materials, while materials such as calcium carbonate and sodium sulfate will affect the barrier properties of the materials and are prone to produce crystal point particles.
[0068] In some preferred embodiments, the components of the modified plastic particles coated with talc powder on the surface include: 50.0 wt % to 80.0 wt % of PPC; 15.0 wt % to 50.0 wt % of PBAT; 2.0 wt % to 5.0 wt % of molecular entanglement agent; 1.0 wt % to 2.0 wt % of talc powder.
[0069] In a preferred embodiment, the melt index of the PBAT used in the outer layer is below 5g / 10min, wherein the test method of the melt index is GB / T3682, and the test conditions are 190°C and 2.16kg; the melting point of the PBAT used in the outer layer is 115-123°C, and the heat deformation temperature is above 55°C;
[0070] In a preferred embodiment, the melt index of the PPC used in the outer layer is below 3g / 10min, wherein the test method of the melt index is GB / T3682, and the test conditions are 170°C and 2.16kg; the thermal decomposition temperature of the PPC used in the outer layer is above 200°C, and the glass transition temperature is above 23°C;
[0071] In some preferred embodiments, the particle size of the talc powder is above 2500 meshes. Preferably, the talc powder may be activated by a silane coupling agent.
[0072] The embodiment of the present invention provides a modification method for preparing the outer layer component, comprising the following steps:
[0073] Step 1: Add PPC, PBAT and molecular entanglement agent into a high-speed mixer in a certain proportion, with a stirring frequency of 20-25 Hz and a stirring time of 3-5 min.
[0074] It should be noted that the high-speed mixer cannot be heated in this step. Preferably, circulating cooling water can be used to keep the temperature below 35°C.
[0075] Step 2: After the mixture is stirred, pour it into the hopper of the twin-screw extruder.
[0076] Among them, the temperature setting of the modification machine is as follows:
[0077] Table 1
[0078]
[0079]
[0080] Among them, the modified bracing rods are cooled by air to prevent the material from absorbing water;
[0081] Step 3: After pelletizing, the pellets are put into a mixing bucket. It is preferred to preheat a certain proportion of talcum powder in the mixing bucket, and stir while pelletizing to coat the surface of the pellets with talcum powder to prevent the pellets from sticking together.
[0082] Step 4: After mixing, bag.
[0083] In some preferred embodiments, the components of the middle layer include PBAT, PLA, activated calcium carbonate, a molecular entanglement agent and calcium stearate.
[0084] The middle layer mainly provides stiffness for the air cushion film and heat resistance for bag making and heat sealing. In order to ensure that the film has good flatness during the bag making process, the film needs a certain stiffness. PLA material is added to the middle layer mainly to increase the hardness of the material so that the film is not easy to wrinkle and deform during stretching and traction.
[0085] Adding activated calcium carbonate can effectively improve the heat resistance of the material, so that there is a certain temperature difference between the middle layer and the inner layer to ensure that the middle layer will not be cracked by heat when the inner layer softens and heat-seals. At the same time, adding calcium stearate can not only promote the dispersion of calcium carbonate materials and reduce the occurrence of thermal degradation of degradable materials during film blowing heating, but also improve the crystallinity of PLA and PBAT materials during cooling and placement, thereby increasing the hardness of the materials. Using the principle of physical winding, the PBAT molecular chains are entangled with the PBAT molecular chains through molecular winding agents.
[0086] In some preferred embodiments, the components of the middle layer include:
[0087] 50.0 wt % to 65.0 wt % of PBAT; 8.0 wt % to 15.0 wt % of PLA; 25.0 wt % to 35.0 wt % of activated calcium carbonate; 2.0 wt % to 5.0 wt % of a molecular entanglement agent; 0.3 wt % to 0.5 wt % of calcium stearate.
[0088] In a preferred embodiment, the melt index of the PBAT used in the middle layer is below 5g / 10min, wherein the test method of the melt index is GB / T3682, and the test conditions are 190°C and 2.16kg;
[0089] In a preferred embodiment, the melt index of the PLA used in the middle layer is below 5 g / 10 min, wherein the test method of the melt index is GB / T3682, and the test conditions are 90° C. and 2.16 kg.
[0090] The embodiment of the present invention provides a modification method for preparing the middle layer component, comprising the following steps:
[0091] Step 1: Add PLA, PBAT, molecular entanglement agent, calcium carbonate and calcium stearate into a high-speed mixer in a certain proportion, set the temperature at 80-85°C, the stirring frequency at 20-25Hz, and the stirring time at 5-10min.
[0092] Step 2: After the mixture is stirred, pour it into the hopper of the twin-screw extruder.
[0093] Among them, the temperature setting of the modification machine is as follows:
[0094] Table 2
[0095] Feeding section Heating section 1 Heating section 2 Heating section 3 Compression section 4 100℃ 120-130℃ 130-140℃ 130-140℃ 130-140℃ Heating section 5 Heating section 6 Extrusion Section Die head Heating section 5 130-140℃ 130-140℃ 130-140℃ 130-140℃ 130-140℃
[0096] Among them, the modified bracing rods are cooled by air to prevent the material from absorbing water;
[0097] Step 3: After granulation, pack into bags.
[0098] In some preferred embodiments, the components of the inner layer include PBAT, PBST, and a lubricant.
[0099] Compared with the middle layer, the inner layer needs to have a lower softening point and better heat sealing performance, so no filler is added to the components of the inner layer. In addition, in order to ensure the adhesion of kraft paper to the film surface at the production reeling position, the material needs to be rolled by a steel wheel at 120-140°C. In order to ensure that the surface of the product is softened and the inner layer is not affected, the inner layer needs to increase a certain softening temperature; since PLA is more likely to affect the final heat sealing property of the material, it is generally considered to add PLA, but PLA and PBAT have poor compatibility and need to be modified to improve compatibility and dispersibility. Based on this, the present invention provides a new idea, that is, a solution of mixing PBAT and PBST together for film blowing, which can not only save the modification operation and cost of the material, but also improve the heat sealing heat resistance of the inner layer. This is because PBAT and PBST have better compatibility, and PBST has higher rigidity and melting point temperature than PBAT, which can provide better heat sealing strength and heat resistance for the inner layer.
[0100] In some preferred embodiments, the components of the inner layer include:
[0101] 49.95 wt % to 65.0 wt % of PBAT; 34.8 wt % to 50.0 wt % of PBST; 0.05 wt % to 0.2 wt % of lubricant.
[0102] In a preferred embodiment, the melt index of the PBAT used in the inner layer is below 5g / 10min, wherein the melt index test method is GB / T3682, and the test conditions are 190°C and 2.16kg;
[0103] In a preferred embodiment, the melt index of the PBST used in the inner layer is below 5 g / 10 min, wherein the test method of the melt index is GB / T3682, and the test conditions are 190° C. and 2.16 kg.
[0104] In a preferred embodiment, the lubricant is an acid amide.
[0105] The embodiment of the present invention provides a modification method for preparing the inner layer component, comprising the following steps:
[0106] Step 1, add PBST, PBAT and lubricant into a high-speed mixer in a certain proportion, without heating, with a stirring frequency of 20-25 Hz and a stirring time of 5-10 min;
[0107] Step 2: Mix the ingredients and put them into bags.
[0108] An embodiment of the present invention provides a method for preparing an air cushion film, comprising the following steps:
[0109] Providing an outer layer component, a middle layer component and an inner layer component, wherein the outer layer component comprises modified plastic particles with talcum powder coated on the surface, and the modified plastic particles comprise PPC, PBAT and a molecular entanglement agent;
[0110] The outer layer component, the middle layer component and the inner layer component are subjected to multi-layer co-extrusion blown film to form a film.
[0111] Specifically, provide materials for the outer layer, middle layer and inner layer, add the above materials to the hopper of the three-layer co-extrusion film blowing machine in sequence, set the inter-layer ratio, set the film blowing temperature, and keep the temperature for 2 hours for film blowing. The specific temperature settings are as follows:
[0112] Table 3
[0113]
[0114]
[0115] The present invention provides a barrier paper air cushion, the barrier paper air cushion comprises an upper protective layer, an air cushion layer and a lower protective layer; the air cushion layer adopts the air cushion film as described above;
[0116] The upper protective layer and the lower protective layer are kraft paper.
[0117] The present invention provides a method for preparing the barrier paper air cushion as described above, comprising the following steps:
[0118] The upper protective layer, the air cushion layer and the lower protective layer are stacked in order from top to bottom and pressed by a heated roller.
[0119] Specifically, the blown tube film is placed on the middle rack, and the upper and lower racks are placed with kraft paper. A special mold is used to heat-seal the surface of the film with patterns such as gourd balls, streamlines, and rectangles, and then pressed with a heated roller. Finally, it is rolled into a finished product. Its appearance is referenced Figure 3 and Figure 4 .
[0120] The following examples are used to illustrate the present invention in more detail but are not intended to limit the present invention in any way.
[0121] The sources of raw materials used in the embodiments of the present invention are as follows, but not limited to the following raw materials: PPC is selected from the brand Zhongke Jinlong, brand T4; PBAT is selected from the brand Xinjiang Tunhe, brand th801; molecular winding agent is selected from the brand Mitsui Chemicals; PLA is selected from the brand Fengyuan, brand 804; silane coupling agent for activation is selected from the brand Jiangxi Guangyuan; calcium stearate is selected from the brand Huamingtai; PBST is selected from the brand Sinopec; intercalated acid amide is selected from the brand Jiangxi Weike.
[0122] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or may be prepared by conventional methods in the art.
[0123] Example 1
[0124] This embodiment provides an air cushion film, including an outer layer, a middle layer and an inner layer;
[0125] (1) A method for modifying an outer layer component, comprising the following steps:
[0126] Step 1: Add 65 parts by weight of PPC particles, 32 parts by weight of PBAT, and 3 parts by weight of molecular entanglement agent into a high-speed mixer, keep the temperature below 35°C, stir at a frequency of 20 Hz, and stir for 3 minutes.
[0127] Step 2: After the mixture is stirred, pour it into the hopper of the twin-screw extruder.
[0128] Among them, the temperature setting of the modification machine is as follows:
[0129] Table 4
[0130] Feeding section Heating section 1 Heating section 2 Heating section 3 Compression section 4 80℃ 110℃ 125℃ 125℃ 125℃ Heating section 5 Heating section 6 Extrusion Section Die head 125℃ 125℃ 125℃ 125℃
[0131] Among them, the modified strands are cooled by air, with a cooling line of 10m to prevent the material from absorbing water;
[0132] Step 3: After pelletizing, the pellets are put into a mixing bucket. 2 parts by weight of talcum powder are preheated in the mixing bucket. The pellets are cut and stirred at the same time so that the talcum powder is wrapped on the surface of the pellets to prevent the pellets from sticking together.
[0133] Step 4: After mixing, bag and set aside.
[0134] (2) A method for modifying the middle layer component, comprising the following steps:
[0135] Step 1: Add 12 parts by weight of PLA, 59.7 parts by weight of PBAT, 3 parts by weight of molecular entanglement agent, 25 parts by weight of calcium carbonate, and 0.3 parts by weight of calcium stearate into a high-speed mixer, set the temperature to 80°C, the stirring frequency to 20 Hz, and the stirring time to 5 min.
[0136] Step 2: After the mixture is stirred, pour it into the hopper of the twin-screw extruder.
[0137] Among them, the temperature setting of the modification machine is as follows:
[0138] Table 5
[0139] Feeding section Heating section 1 Heating section 2 Heating section 3 Compression section 4 100℃ 125℃ 135℃ 135℃ 135℃ Heating section 5 Heating section 6 Extrusion Section Die head 135℃ 135℃ 135℃ 135℃
[0140] Among them, the modified strands are cooled by air, with a cooling line of 10m to prevent the material from absorbing water;
[0141] Step 3: After granulation, pack into bags for later use.
[0142] (3) A method for modifying the inner layer component, comprising the following steps:
[0143] Step 1: Add 50 parts by weight of PBST, 48.8 parts by weight of PBAT and 0.2 parts by weight of dielectric amide into a high-speed mixer without heating, with a stirring frequency of 20 Hz and a stirring time of 5 min.
[0144] Step 2: After the mixture is stirred, bag it for later use.
[0145] (4) The materials prepared from the outer layer, middle layer and inner layer components are sequentially added to the hopper of the three-layer co-extrusion film blowing machine, the interlayer ratio is set, the film blowing temperature is set, and the film is blown for 2 hours at a temperature of 2 hours. The specific temperature setting is as shown in the following table:
[0146] Table 6
[0147] Serial number Heating section 1 Heating section 2 Heating section 3 Compression section 4 Heating section 5 Die head A floor 100℃ 145℃ 145℃ 145℃ 145℃ 145℃ B-tier 120℃ 160℃ 160℃ 160℃ 160℃ 160℃ C-tier 120℃ 145℃ 145℃ 145℃ 145℃ 145℃
[0148] (5) Place the blown tube film on the middle rack, place kraft paper on the upper and lower racks, use a special mold to heat-seal patterns such as gourd balls, streamlines, rectangles, etc. on the surface of the film, and press it with a heating roller. The temperature of the heating roller is 120°C, and finally it is rolled into a finished product.
[0149] Example 2
[0150] This embodiment is similar to embodiment 1, except that the molecular entanglement agent is replaced with 0.2 parts by weight of chain extender BASF 4468.
[0151] Example 3
[0152] This embodiment is similar to embodiment 1, except that the molecular entanglement agent is replaced with 10 parts by weight of maleic anhydride grafted PBAT compatibilizer.
[0153] Example 4
[0154] This embodiment is similar to embodiment 1, except that no polymer entanglement agent is added.
[0155] The products obtained in Examples 1-4 were subjected to surface observation, longitudinal tensile strength, longitudinal tensile strength after aging at 80° C. for 72 hours, and oxygen permeability tests respectively;
[0156] Among them, surface observation (abbreviated as: appearance) is: visually inspecting the number of particles larger than 0.5 mm in a unit area (50*50 cm); longitudinal tensile strength (MPa) is: tested in accordance with the test standard of GB / T1040.3-2006; longitudinal tensile strength (Mpa) after aging at 80°C for 72 hours is: tested in accordance with the test standard of GB / T1040.3-2006; oxygen permeability (cm 3 / (m 2 *24H*0.1MPa)) is: tested in accordance with the test standard of ASTM D1434-82.
[0157] The performance test results are shown in the following table:
[0158] Table 7
[0159] project Appearance Longitudinal tensile strength Longitudinal tensile strength after aging at 80℃ for 72 hours Oxygen permeability Example 1 0 36 34 86 Example 2 17 28 26 — Example 3 8 26 22 204 Example 4 0 18 11 382
[0160] It can be seen from the above table that both Example 1 with the addition of a molecular entanglement agent and Example 4 without the addition of a compatibilizer have no crystal point problem. However, Example 4 without the addition of a compatibilizer has poor performance and poor inter-material desirability.
[0161] Although both Examples 2 and 3 have the effect of improving material compatibility, they both have different degrees of crystal points. Among them, the chain extender 4468 used in Example 2 reacts particularly violently. In terms of performance, the molecular entanglement agent has the best compatibility with the chain extender 4468, and the performance is relatively better. The performance after aging is also particularly obvious. However, in Example 2, the chain extender causes perforation due to the crystal point problem, resulting in barrier failure;
[0162] It can be seen that the use of the molecular entanglement agent in the present invention can provide material compatibility without forming crystal points.
[0163] Example 5
[0164] This embodiment is similar to embodiment 1, except that the talc in the outer layer component is replaced with 2000 mesh activated calcium carbonate.
[0165] Example 6
[0166] This embodiment is similar to embodiment 1, except that no talc is added to the composition of the outer layer.
[0167] Example 7
[0168] This embodiment is similar to embodiment 1, except that the talc in the outer layer component is replaced with 0.4 parts by weight of mesic acid amide.
[0169] The products obtained in Example 1 and Examples 5-7 were respectively subjected to surface observation, longitudinal tensile strength, longitudinal tensile strength after aging at 80° C. for 72 hours, and oxygen permeability tests;
[0170] Among them, surface observation (abbreviated as: appearance) is: visually inspecting the number of particles larger than 0.5 mm in a unit area (50*50 cm); longitudinal tensile strength (MPa) is: tested in accordance with the test standard of GB / T1040.3-2006; longitudinal tensile strength (Mpa) after aging at 80°C for 72 hours is: tested in accordance with the test standard of GB / T1040.3-2006; oxygen permeability (cm 3 / (m 2 *24H*0.1MPa)) is: tested in accordance with the test standard of ASTM D1434-82.
[0171] The performance test results are shown in the following table:
[0172] Table 8
[0173] project Appearance Longitudinal tensile strength Longitudinal tensile strength after aging at 80℃ for 72 hours Oxygen permeability Example 1 0 36 34 86 Example 5 5 32 33 152 Example 6 - - - - Example 7 - - - -
[0174] As can be seen from the table above, although calcium carbonate is used to replace talcum powder in Example 5, it also plays a role in preventing particles from sticking, but because calcium carbonate itself does not have a smooth effect, it cannot be evenly dispersed in the material in the case of single-screw plasticizing and blowing film, resulting in local crystal points and small particles. And because of its granular structure, it will also affect the barrier properties of the material to a certain extent.
[0175] In Example 6, without the addition of talcum powder, the particles would adhere together and be unusable.
[0176] In Example 7, the use of mesoamide to replace talcum powder has a certain anti-sticking effect, but because its dosage is too small, the uniformity of the wrapped particles is poor, and it is difficult to completely solve the problem of adhesion between particles. If the amount of mesoamide added is further increased, on the one hand, it will generate a higher cost burden, and more importantly, the mesoamide will precipitate later, affecting the use of the film, resulting in film sticking problems and the problem of being unable to heat seal with kraft paper.
[0177] Example 8
[0178] This embodiment is similar to embodiment 1, except that calcium stearate is not added to the components of the middle layer.
[0179] Example 9
[0180] This embodiment is similar to embodiment 1, except that no activated calcium carbonate is added to the composition of the middle layer.
[0181] Example 10
[0182] This embodiment is similar to embodiment 1, except that PLA is not added to the composition of the middle layer.
[0183] The products obtained in Example 1 and Examples 8-10 were tested for heat seal burst temperature, surface observation, and longitudinal tensile strength respectively;
[0184] The heat seal burst temperature is the temperature at which the film breaks under a horizontal tensile force of 10N and a vertical heat seal pressure of 10kg. The surface observation (abbreviated as: appearance) is the number of particles larger than 0.5mm in a unit area (50*50cm) visually inspected. The longitudinal tensile strength (MPa) is tested in accordance with the test standard of GB / T1040.3-2006.
[0185] The performance test results are shown in the following table:
[0186] Table 9
[0187] project Heat seal bursting temperature Appearance Longitudinal tensile strength Example 1 125 0 36 Example 8 120 10 35 Example 9 118 0 38 Example 10 123 0 28
[0188] It can be seen from the above table that after calcium stearate was not added to Example 8, the hot melt temperature dropped by 5°C, and the dispersion of calcium carbonate became worse, and a crystal point problem occurred. It can be seen that calcium stearate not only has the effect of improving the thermal stability of the material, but also can improve the dispersion of the powder.
[0189] Although the longitudinal tensile strength of Example 9 was slightly improved after calcium carbonate was not added, the heat seal burst temperature decreased to a certain extent.
[0190] Due to the lack of PLA, the performance of Example 10 is significantly reduced, the strength is reduced, and the material becomes soft.
[0191] Embodiment 11
[0192] This example is similar to Example 1, except that the amount of PPC added to the outer layer component is reduced to 30 wt%.
[0193] Example 12
[0194] This example is similar to Example 1, except that the amount of PPC added to the outer layer component is reduced to 40 wt%.
[0195] Example 13
[0196] This example is similar to Example 1, except that the amount of PPC added to the outer layer component is reduced to 50 wt%.
[0197] Embodiment 14
[0198] This example is similar to Example 1, except that the amount of PPC added to the outer layer component is increased to 80 wt%.
[0199] Embodiment 15
[0200] This embodiment is similar to embodiment 1, except that the amount of PPC added to the outer layer component is increased to 90 wt%.
[0201] The products obtained in Example 1 and Examples 11-15 were tested for the composite strength between the kraft paper non-heat-sealed line area and the film; the performance test results are shown in the following table:
[0202] Table 10
[0203]
[0204] As can be seen from the table above, when the amount of PPC added in Example 11 was reduced to 30% by weight, the film had insufficient adhesion to the kraft paper after hot pressing by the roller;
[0205] Example 12: With the increase of the amount of PPC added, the adhesion of the film to the kraft paper was improved after hot pressing by the roller, but it was still difficult to meet the requirements;
[0206] Example 13, when the amount of PPC added is increased to 50% by weight, the film has a significantly increased adhesion to the kraft paper after hot pressing by the roller, and can meet the use requirements;
[0207] Example 14, when the addition amount of PPC is further increased to 80% by weight, the adhesion of the film to the kraft paper begins to decline after hot pressing by the roller, but it still meets the use standard;
[0208] In Example 15, when the addition amount of PPC is increased to 90% by weight, the adhesion of the film to the kraft paper begins to drop significantly after hot pressing with a roller, because it is too sticky and has lost its strength, and cannot meet the requirements.
[0209] It can be seen that for the technical solution of the outer layer of the present invention, the content of PPC is best between 50 wt % and 80 wt %.
[0210] Example 16
[0211] This embodiment is similar to embodiment 1, except that PBST in the inner layer component is replaced with PBAT.
[0212] Embodiment 17
[0213] This embodiment is similar to embodiment 1, except that the PBST in the inner layer component is replaced by PLA.
[0214] The products obtained in Example 1 and Examples 16-17 were tested for inner mucosal layer test, film inner layer heat sealing strength, and longitudinal tensile strength respectively; the performance test results are shown in the following table:
[0215] Table 11
[0216]
[0217] As can be seen from the above table, the inner layer component of Example 16 was replaced by PBAT from PBST. After the film was pressed by a roller at 130°C, a sticky film phenomenon appeared in the inner layer of the film, and the product could not be inflated;
[0218] The inner layer component of Example 17 was replaced by PLA from PBST. After the film was pressed by a roller at 130°C, although there was no sticky film on the inner layer of the film, the heat sealing strength decreased significantly, which seriously affected the performance of the air cushion product.
[0219] It can be seen that PBST can not only increase the softening temperature of the inner layer and avoid the inner layer sticking during hot pressing by the roller, but also will not affect the heat sealing performance of the material itself.
[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An air cushion film, characterized in that: The air cushion film comprises an outer layer, a middle layer and an inner layer; The components of the outer layer include modified plastic particles with talcum powder coated on the surface, and the components of the modified plastic particles include PPC, PBAT and a molecular entanglement agent; The components of the middle layer and the inner layer both contain PBAT.
2. The air cushion film according to claim 1, characterized in that: The components of the modified plastic particles coated with talcum powder on the surface include: 50.0 wt. % to 80.0 wt. % PPC; 15.0 wt % to 50.0 wt % PBAT; 2.0 wt % to 5.0 wt % of a molecular entanglement agent; 1.0 to 2.0 wt% talc.
3. The air cushion film according to claim 1, characterized in that: The particle size of the talcum powder is above 2500 meshes.
4. The air cushion film according to claim 1, characterized in that: The components of the middle layer include PBAT, PLA, activated calcium carbonate, a molecular entanglement agent and calcium stearate.
5. The air cushion film according to claim 4, characterized in that: The components of the middle layer include: 50.0 wt % to 65.0 wt % PBAT; 8.0 to 15.0 wt % PLA; 25.0 to 35.0 wt. % activated calcium carbonate; 2.0 wt % to 5.0 wt % of a molecular entanglement agent; 0.3 wt% to 0.5 wt% calcium stearate.
6. The air cushion film according to claim 1, characterized in that: The components of the inner layer include PBAT, PBST and a lubricant.
7. The air cushion film according to claim 6, characterized in that: The components of the inner layer include: 49.95 wt % to 65.0 wt % PBAT; 34.8 wt % to 50.0 wt % PBST; 0.05 wt % to 0.2 wt % of a lubricant.
8. A method for preparing an air cushion film, characterized in that: The following steps are involved: Providing an outer layer component, a middle layer component and an inner layer component, wherein the outer layer component comprises modified plastic particles with talcum powder coated on the surface, and the modified plastic particles comprise PPC, PBAT and a molecular entanglement agent; The outer layer component, the middle layer component and the inner layer component are subjected to multi-layer co-extrusion blown film to form a film.
9. A barrier paper air cushion, characterized in that: The barrier paper air cushion comprises an upper protective layer, an air cushion layer and a lower protective layer; The air cushion layer adopts the air cushion film as described in any one of claims 1 to 7; The upper protective layer and the lower protective layer are kraft paper.
10. The method for preparing the barrier paper air cushion according to claim 9, characterized in that: The following steps are involved: The upper protective layer, the air cushion layer and the lower protective layer are stacked in order from top to bottom and pressed by a heated roller.
Citation Information
Patent Citations
Bubble cushion packaging composite film, preparation method thereof and bubble bag
CN111890770A
Biodegradable PBAT / PPC foamed composite material and preparation method thereof
CN112662146A
Completely degradable air-blocking air cushion film with excellent processability, and preparation method thereof
CN112959782A
Multilayer biodegradable air bubble film and preparation process thereof
CN115257112A
Biodegradable wrapping film as well as preparation method and application thereof
CN117210159A
Cited By
Paper air cushion
CN223200698U